2014
DOI: 10.3892/ijmm.2014.1755
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide/adenosine triphosphate induces IL-1β and IL-18 secretion through the NLRP3 inflammasome in RAW264.7 murine macrophage cells

Abstract: Abstract. The NOD-like receptor family, pyrin domaincontaining 3 (NLRP3) inflammasome plays pivotal roles in inflammation and autoimmunity. The NLRP3 inflammasome is activated in response to various signals, including pathogenassociated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs). However, its role in inflammation remains unclear. In this study, we used lipopolysaccharide (LPS) and adenosine triphosphate (ATP) to simulate an inflammatory environment as the testing model. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 50 publications
6
34
0
1
Order By: Relevance
“…Previous studies showed that stimulation by LPS plus ATP could trigger the activation of NLRP3 inflammasome in RAW264.7 cells [38, 39]. Here, we observed that exposure to hyperoxia could result in NLRP3 inflammasome activation in RAW264.7 cells, which was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that stimulation by LPS plus ATP could trigger the activation of NLRP3 inflammasome in RAW264.7 cells [38, 39]. Here, we observed that exposure to hyperoxia could result in NLRP3 inflammasome activation in RAW264.7 cells, which was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, exposure to bacterial lipopolysaccharide (LPS) induces an inflammatory phenotype in macrophages that is characterised by the expression of many proinflammatory cytokines including TNF-α and IL-1β [4]. The proinflammatory activities of macrophages is also associated with activation of NLR Family Pyrin Domain Containing 3 (NLRP3)-dependent inflammasome [5] and the nuclear transcription factor, NF-κB [6]. During the resolution of inflammation, macrophages produce mediators such as IL-10 and Interleukin-1 receptor antagonist (IL-Ra), that in turn, down-regulate inflammatory processes [7].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with these reports, our results also implicate the overexpression of ATF3 in the reduction of the mRNA and the secretion of TNF‐α, IL‐1β, and IL‐6 in RAW264.7, as well as mouse peritoneal macrophages. IL‐18 is a pro‐cytokine and induced by LPS in RAW264.7 murine macrophage cells . Moreover, the IL‐18 in BALF was increased after infected with Streptococcus pneumonia in mice .…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a pro-cytokine and induced by LPS in RAW264.7 murine macrophage cells. 29 Moreover, the IL-18 in BALF was increased after infected with Streptococcus pneumonia in mice. 30 Prior study reported that was up-regulated in patients with MPP compared to no infected.…”
Section: Mp Infection Shows a Variety Of Clinical Manifestations Ranmentioning
confidence: 97%